Arthur White Collection, Correspondence from Time Magazine Medicine to London division, July 18, 1978. - Unknown, Newsdesk (AB) (Time Magazine; Digitized from original print, Valdosta State University Archives and Special Collections, November 29, 2016., 1978)
Correspondence from London division to Time Magazine, Medicine Edition in reference to the impending birth of the first "test-tube baby" by Lesley and John Brown in Oldham, England in 1978 by doctors Patrick Steptoe (Gynecologist) and Robert Edwards (Physiologist).
Digitized from original print, Valdosta State University Archives and Special Collections, November 29, 2016.
Keywords: Test tube baby; Arthur White; Time Magazine; Time Magazine Medicine; Time Press; In Vitro Fertilization; IVF; Steptoe-Edwards Fertilization Technique; 1970s; 1978; Lesley Brown; John Brown; Lousie Joy Brown; Oldham General Hospital; Oldham, England; England; Great Britain; Patrick Steptoe; Professor Sir Robert Edwards; Robert Edwards; London, England